PENGARUH BUDAYA KERJA TERHADAP KEJADIAN KECELAKAN AKIBAT KERJA PADA PROYEK DI SMK SEHATI KABUPATEN KARAWANG - Wendi Darmawan; Chaerani Tri Yuliana; Jumaedi, Jumaedi; Muhidin, Muhidin; Wieke Widhiantika (Journal of Innovation Research and Knowledge, 2024)
This study aims to explore the influence of work culture on the frequency of work accidents in construction projects carried out by construction workers at SMK Sehati, Karawang Regency. A good work culture is seen as a key factor in creating a safe working environment and minimizing accident risks. A quantitative survey method was used to collect data from construction workers, focusing on their perceptions of work culture and compliance with safety procedures, such as the use of Personal Protective Equipment (PPE). The results show that the majority of workers rate the work culture at SMK Sehati as "Good" or "Very Good," contributing to the low frequency of work accidents. Additionally, the high level of PPE usage among workers indicates good awareness of safety importance. Regression analysis revealed a negative correlation between the quality of work culture and the frequency of accidents, confirming that improvements in work culture can significantly reduce accident incidents. Based on these findings, it is recommended that SMK Sehati continues to strengthen its work culture through regular training, periodic safety audits, and strict supervision of PPE usage. The implementation of these recommendations is expected to further enhance work safety in future construction project